Multilingualism and the periphery - Sari Pietikäinen; Helen Kelly-Holmes (2013)
This volume examines the complexities of the processes and practices of multilingualism in a wide range of economic, cultural, political and physical peripheral sites and spaces (tourism, education, indigenous and minority language rights and politics, gender relations, marketing, airports) in different geographic locations (Austria, Canada, Corsica, Catalonia, Finland, Ireland, Patagonia, Spain, Slovenia, U.S.A., Wales). Using approaches that draw on sociolinguistics, discourse studies and ethnography, different peripheral indigenous and minority language sites varying from Arctic territories to a busy airport in Wales are examined. The volume brings together these different contexts and approaches in order to explore what kind of possible commonalities and differences might arise from processes of peripheralizing and centralising in multilingual indigenous and minority language sites. The perspective opens up new ways of thinking and theorising about multilingualism and about cores and peripheries, and necessarily involves a challenge to existing notions of straightforward power relations (e.g. majority-minority; centre-periphery etc.). It questions assumptions about peripheries as less fortunate counterparts to prosperous centres, and suggests instead that peripheries are diverse, multilingual spaces, constructed by but, crucially, constitutive to cores.